(untitled) (المجلة العراقية للعلوم الاقتصادية, 2018)
The currency auction managed by the Central Bank of Iraq plays an important role in maintaining the stability of the Iraqi dinar exchange rate against the dollar, and it is an important tool to maintain low levels of inflation. However, the currency auction in the light of the dertermined exchange rate had an impact on the depletion of foreign reserves, increasing imports from abroad; the currency auction also raised the issue of money supply, due to excessive liquidity caused by the auction. The currency auction represents a burden on foreign reserves, due to the increase in the according demand for reserves for the purpose of meeting multiple requirements, such as imports, tourism, study and treatment, in addition to the flight of capital. The study recommended the need to establish a joint public-private bank, in accordance with a mechanism to reduce the dissipation of foreign reserves. المقدمة